2020
DOI: 10.1186/s13287-020-01730-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mesenchymal stem cell therapy for sepsis: a meta-analysis of preclinical studies

Abstract: Background: Multiple studies have reported that mesenchymal stem cell (MSC) therapy has beneficial effects in experimental models of sepsis. However, this finding remains inconclusive. This study was performed to systematically determine the connection between MSC therapy and mortality in sepsis animal models by pooling and analyzing data from newly published studies. Methods: A detailed search of related studies from 2009 to 2019 was conducted in four databases, including MEDLINE, EMBASE, Cochrane Library, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 48 publications
1
39
1
Order By: Relevance
“…There are other potential therapies for the clinics, such as microbiological guided therapy, including fecal microbiota transplantation (FMT) or probiotic therapy [ 85 – 87 ]. Previous studies of our team have found that the use of stem cells significantly reduces the mortality of septic rats and mice [ 21 , 27 , 74 ]. In future sepsis research, our team will continue to focus on the potential treatment and explore the treatment mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other potential therapies for the clinics, such as microbiological guided therapy, including fecal microbiota transplantation (FMT) or probiotic therapy [ 85 – 87 ]. Previous studies of our team have found that the use of stem cells significantly reduces the mortality of septic rats and mice [ 21 , 27 , 74 ]. In future sepsis research, our team will continue to focus on the potential treatment and explore the treatment mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies also found that ADMSCs attenuate sepsis-related ALI by releasing sTNFR1 [ 21 ]. ADMSCs can alleviate inflammation and oxidative stress [ 22 , 23 ], and many studies have confirmed the therapeutic effect of mesenchymal stem cells (MSCs) in sepsis animal models [ 24 27 ]. Furthermore, MSCs can inhibit the MAPK pathway activation during sepsis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although MSC therapy was associated with improved outcomes such as faster hemodynamic stabilization, vasodepressor withdrawal, improvement in respiratory failure and decrease in neutropenic period, it did not prevent death from the sepsis related organ failure [101]. However, a meta-analysis study evaluating the efficacy of MSC therapies in animal models of sepsis demonstrated lower mortality rates underlining the potential therapeutic effects of MSCs in sepsis and the need for future studies [102]. On the other hand, EVs as cell-free agents and/or drug carriers may have therapeutic functions in sepsis.…”
Section: Acute Respiratory Distress Syndromementioning
confidence: 99%
“…Despite the report of contradictory results, a recent metaanalysis of 29 animal studies, including 1266 animals, demonstrated that MSC therapy was related to a significant lower mortality rate. 32 Moreover, cell tracing studies performed in rodents exhibited that MSCS distribute to a variety of tissues after IV infusion. They were found in the lung early after administration, then in the liver and the spleen.…”
Section: Mscs and Sepsis Including The Context Of Covid-19mentioning
confidence: 99%
“…However, they did not observe either any beneficial effect of MSCs on organ failures, unlike us. Despite the report of contradictory results, a recent meta‐analysis of 29 animal studies, including 1266 animals, demonstrated that MSC therapy was related to a significant lower mortality rate 32 . Moreover, cell tracing studies performed in rodents exhibited that MSCS distribute to a variety of tissues after IV infusion.…”
Section: Mscs and Sepsis Including The Context Of Covid‐19mentioning
confidence: 99%